2017
DOI: 10.1017/jse.2017.5
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Prevalence in Students With Autism Spectrum Disorder

Abstract: All forms of bullying, physical, verbal, social, and cyber, are prevalent among youth worldwide. An especially vulnerable population for involvement in bullying is students with an autism spectrum disorder (ASD). Although there are some studies that have investigated bullying in these students, many of these are beset by methodological issues. We surveyed 104 students with ASD on their bullying experiences in all 4 forms of bullying and examined their roles as victim, perpetrator, and bully-victim, comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 60 publications
0
10
0
1
Order By: Relevance
“…Further, children with ADHD also exhibit externalizing symptoms, including impulsivity, attention problems, and aggression, which are traits that peers and parents may find aversive and that will lead to difficulties with socialization and caregiving demands [7]. Much of the earlier peer victimization research has identified these characteristics as risk factors for peer victimization involvement and found that children with ASD and ADHD are especially prone to social victimization [48,67]. As Rose and Espelage [68] have argued, it is not the disability itself that is a risk factor but the characteristics associated with the disability.…”
Section: Discussionmentioning
confidence: 99%
“…Further, children with ADHD also exhibit externalizing symptoms, including impulsivity, attention problems, and aggression, which are traits that peers and parents may find aversive and that will lead to difficulties with socialization and caregiving demands [7]. Much of the earlier peer victimization research has identified these characteristics as risk factors for peer victimization involvement and found that children with ASD and ADHD are especially prone to social victimization [48,67]. As Rose and Espelage [68] have argued, it is not the disability itself that is a risk factor but the characteristics associated with the disability.…”
Section: Discussionmentioning
confidence: 99%
“…Percentage agreement between the authors was 93% for English articles and 100% for Japanese and Korean studies. Supplementary Table 1 (only online) 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 for a final list of the reviewed studies.…”
Section: Search and Selection Of Studiesmentioning
confidence: 99%
“…Autistic individuals universally experience difficulties with social communication and in social development, and often display ritualistic and stereotypical behaviours, resistance to change, and sensory sensitivities (American Psychiatric Association 2013). These social, communication, and behavioural difficulties place this population at an increased risk for social exclusion compared to children with none and/or other disabilities (Campbell et al 2017;Hebron, Humphrey, and Oldfield 2015;Symes 2010, 2011;J. Schroeder et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Of concern is that low social acceptance increases the risk of victimisation in the neurotypical population (Godleski et al 2015;Veenstra et al 2007Veenstra et al , 2010; and research suggests that for children with autism there is a four-fold likelihood of experiencing bullying (Campbell et al 2017;J. Wainscot et al 2008a), and an increased likelihood relative to other disability groups (e.g.…”
Section: Introductionmentioning
confidence: 99%